George P. Moschis tribute special issue: His philosophy and contributions (Part II). Issue 1 (2nd January 2020) - Mathur, Anil
ABSTRACT: This is the second part of the George P. Moschis tribute special issue. In this part, I briefly present the gist of contributions made by each article included in this second part of the special issue.